2018
DOI: 10.1002/ejhf.1135
|View full text |Cite
|
Sign up to set email alerts
|

Who needs an implantable cardioverter‐defibrillator? Controversies and opportunities after DANISH

Abstract: Since the publication of DANISH, the largest ever trial of implantable cardioverter-defibrillators (ICDs) in patients with non-ischaemic heart failure (HF), cardiologists are less certain which of their patients should receive an ICD. 1 Earlier in the same year (2016) that this trial was presented and published, the European Society of Cardiology HF guidelines gave a class IB recommendation for ICDs in non-ischaemic New York Heart Association class II/III HF with an ejection fraction <35%. 2 After this large, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, no difference in mortality has yet been reported among DCM patients with and without ICD implantation in any randomized trial. A subgroup analysis of the SCD-HeFT trial had only reported a trend towards reduced mortality in DCM [ 4 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no difference in mortality has yet been reported among DCM patients with and without ICD implantation in any randomized trial. A subgroup analysis of the SCD-HeFT trial had only reported a trend towards reduced mortality in DCM [ 4 ] .…”
Section: Discussionmentioning
confidence: 99%
“…So far, there have been no randomized trials of ICD versus control group that reported a reduction in all-cause mortality in patients with DCM. Only a subgroup analysis of the Sudden Cardiac Death in Heart Failure Trial (SCD-HeFT) showed a trend towards reduced mortality in these patients [ 4 ] . Recently, the Danish Study to Assess the Efficacy of ICDs in Patients with Non-ischemic Systolic Heart Failure on Mortality (DANISH) trial showed no reduction in the primary endpoint of all-cause mortality among ICD recipients [ 5 ] .…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of this situation has been compounded by the revolution in prognostic therapies for LVSD with or without heart failure over the past three decades, which means that the absolute validity of historical trial evidence is open to question. It is increasingly obvious that new RCTs are necessary, and the possible variations upon these are extensive [ 49 ]. What remains to be seen is how far trial investigators will dare to go in re-challenging the evidence base.…”
Section: Discussionmentioning
confidence: 99%
“…Potential reasons for lack of survival benefit may be inappropriate selection in non-arrhythmogenic DCM genotypes and exclusion of genetic DCM where malignant ventricular arrhythmias occur in individuals with only mild or moderate reductions in ejection fraction [5]. Collectively, these findings have prompted review of indications for ICD use, particularly in the setting of non-ischaemic heart failure, and have highlighted the need to identify subsets of high-risk patients who might derive the greatest benefit from ICD implantation for the primary prevention of sudden cardiac death [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%